Conceptualizing Semi‐Legality in Migration Research. Issue 3 (22nd July 2013) - Kubal, Agnieszka
<x xml:space="preserve">Abstract</x> What is semi‐legality, and why does it offer a viable alternative to the legality–illegality binary divide? Semi‐legality, as a heuristic device, is useful to frame the various "in‐between" statuses and not resorting to illegality every time ambiguities arise as this casts the net of potential fraud far too wide. It could be viewed as a multidimensional space where migrants' formal relationships with the state interact with their various forms of agency toward the law. As a sensitizing theoretical perspective, it helps to explain why many neoliberal regimes, which claim that law and order are the main features distinguishing them from others, actually engage in perpetuating the legally ambiguous modes of incorporation. Delineating the conditions of semi‐legality, I use data from 360 qualitative interviews with migrants in four European countries. I discuss: (1) "incomplete" responses to regularization programs (amnesties) – de facto fulfilling the legalization conditions, yet facing barriers to formally (de jure) corroborate this; (2) balancing between the temporality of residence in various EU countries—under‐staying in some and overstaying in others; and (3) the nexus with employment—where migrants' residence in a country is lawful, but their work exceeds the restrictions permitted by their visas.